Optimization of elm regeneration in vitro using leaf esplants and evaluation of the proceá in transformation experiments - Dorion, M.=700 1 Ben Jouira, H.; Jouanin, L.
(Es, En)
ilus., 42 ref.
Keywords: ULMUS; REGENERACION IN VITRO; MEDIO DE CULTIVO; NEOMICINA; ESPAÑA